ダイ 25ジ ナンキョク チイキ カンソクタイ ナツタイ ホウコク 1983-1984 - 内藤, 靖彦; ナイトウ, ヤスヒコ; Naito, Yasuhiko (1999)
P(論文) 第25次南極地域観測隊は越冬隊36名, 夏隊11名の構成のもと, 1983年11月14日東京港を出発した。25次隊には観測隊員以外に, 本部委員1名, 外国交換科学者1名(アメリカ), 報道関係者5名(新聞取材2名, テレビ取材3名), 造船関係者5名の計12名が同行した。「しらせ」就航により輸送量の増大や早期の接岸が期待され, 新発電棟設備の工事など多くの夏作業が計画された。12月14日には氷縁に到着したが, 18日には昭和基地北42.7マイル地点で厚さ10mに及ぶハンモックアイス帯に遭遇し, 輸送の遅れが懸念された。幸いハンモックアイス帯を無事突破, 1月5日には6年ぶりに接岸に成功し774トンの物資輸送を行った。昭和基地方面における新発電棟関連の工事などすべての活動を1月末までに終了し, 「しらせ」は2月1日反転北上, セールロンダーネ山地地学調査のためブライド湾に向った。2月3日よりL0,30マイル拠点への輸送, 雪上車組立, 小屋設置の諸作業を行った後, 地学旅行隊は12日から23日の期間で調査を実施した。地学調査と並行し「しらせ」はブライド湾, グンネルスバンク域において海洋観測を実施した。乗員に患者が発生したため予定を変更し, 2月23日反転北上し, ケープタウンに向かった。2月3日ケープタウン入港, 患者は無事下船, 2月5日ポートルイスに向け出港した。以後ポートルイス, シンガポール経由し予定通り4月19日東京港に戻り, 25次隊の行動を終了した。 The 25th Japanese Antarctic Research Expedition (JARE-25) consisted of 36 wintering members and 11 summer members. The summer party was accompanied by one observer from JARE headquarters, one foreign exchange scientist from the U.S.A., 2 press observers, 3 TV crews, and 5 ship engineers. The icebreaker "Shirase" left Tokyo on November 14,1983 as her first voyage to Antarctica and arrived at the pack ice edge near Lutzow-Holm Bay on December 14. On December 18 she encountered a heavy hummock ice zone at the mouth of Lutzow-Holm Bay. She managed to break through it and succeeded to anchor at Syowa Station. She off loaded 774 tons of cargo there. Logistic operations such as construction of a new power house, the new power system in it and observation facilities progressed on the planned schedule and "Shirase" left there on February 1,1984 for Breid Bay to support geological field survey at Sor Rondane Mountains and to conduct oceanographic survey. "Shirase" stayed in Breid Bay and adjacent waters from February 3 to February 23. Thereafter she changed her destination to Cape Town, South Africa, to carry a patient. She arrived in Cape Town on March 3 and left there March 4 for Tokyo via Port Louis, Mauritius and Singapore. Wintering members of JARE-24 and some observers left the ship at Port Louis. Along her cruise track she conducted oceanographic observations as planned. ...